Low-quality straw over high-quality straw preferred for mineral-associated organic matter formation - Xiaofang Ji; Dengchun Xing; Xin Guan; Yugang Wang; Gilles Colinet; Wenting Feng (Geoderma)
The formation of mineral-associated organic matter (MAOM) from plant litter decomposition is crucial for climate change mitigation. However, the way in which plant litter of varying qualities influences MAOM formation and decomposition, particularly regarding the quantity of litter inputs, remains largely unclear. This study aimed to determine how the quality of straw, specifically low-quality wheat (Triticum aestivum L.) versus high-quality milk vetch (Astragalus sinicus L.), and its quantity (input level) affect MAOM formation and decomposition. We conducted a 420-day laboratory incubation experiment using low-quality wheat versus high-quality milk vetch straws added to artificial soil (pure quartz vs. soil with reactive minerals (sandy soil: 5 % clay, 10 % silt, and 85 % sand)) at input levels of 0, 3, 6, 18, 26, 31, and 35 g C kg−1 soil. Different from the Microbial Efficiency-Matrix Stabilization theory, our research indicates that adding low-quality wheat straw led to significantly greater MAOM content than high-quality milk vetch. Notably, the MAOM stabilization efficiency declined at high input levels (26, 31, and 35 g C kg−1 soil) for wheat than for milk vetch. This is further supported by the evidence that reactive minerals slowed the decomposition rate of low-quality wheat straw more effectively than that of high-quality milk vetch. Moreover, the lower C/N ratio of the MAOM fraction, the reduced C/N ratio of dissolved organic matter (DOM), and a higher fluorescence index of DOM (higher values indicating greater contribution of microbial sources) after adding milk vetch than adding wheat straw suggest the significant role of plant-derived organic matter in MAOM formation. Our findings disclose that reactive minerals preferentially protect low-quality litter over high-quality litter through direct interaction with plant-derived organic matter, providing a critical pathway for MAOM formation distinct from microbial assimilation. This study highlights the key role of low-quality straw in the efficient and long-term stabilization of soil C within agricultural practices.